PENILAIAN TEKSTUR DAN TINGKAT KESUKAAN KASTENGEL DENGAN SUBSTITUSI TEPUNG GARUT (Maranta arundinacea) - Rahmadewi, Yunda Maymanah; Wijayanti, Harwi; Nurrochmah, Shinta (Jurnal Sains dan Teknologi Pangan, 2023)
The purpose of this study was to determine the effect of arrowroot flour substitution on the degree of friability, hardness, and stickiness of kastengel as well as the preference level of color, taste, aroma, texture, and overall preference of kastengel. This study used a completely randomized design (CRD). Substitution in this study was arrowroot flour as much as 5 levels, namely K0 (0% arrowroot flour: 100% flour), K1 (25% arrowroot flour: 75% flour), K2 (50% arrowroot flour: 50% flour), K3 (50% arrowroot flour 75% arrowroot: 25% flour, and K4 (100% arrowroot flour: 0% flour). Data were analyzed using analysis of variance, the results of organoleptic assessment which had a significant effect on the observed variables, followed by the Least Significant Difference (LSD) test at 95% confidence level (α = 0.05). Substitution of arrowroot flour as a substitute for wheat with different amounts in kastengel products results in different texture assessments for the parameters of crumbness, hardness, and stickiness. Substitution of flour with arrowroot flour had a significant effect on the color of the chestnut but did not have a significant effect on the aroma, taste, texture and overall preference. Arrowroot flour substitution of 25% (K1) gave the highest level of preference for color, taste, and overall preference. Meanwhile, the highest average preference rating for the aroma attribute was seen in the kastengel without substitution (K0) and the texture attribute in the kastengel without flour (K4).